The role of musical pitch in long-distance defensive signaling - Podlipniak, Piotr (Wiley Periodicals LLC, 2025)
Many species use conspicuous sound signaling as a defense strategy against conspecifics and heterospecifics. This has prompted some scholars to hypothesize that musical displays can serve as a defensive signaling mechanism. It has been suggested that to achieve this function, hominins may have used synchronized acoustic signals, which then became the roots of musical rhythm. Another important component of music—pitch—has been proposed to result either from other selective pressures or as a byproduct of certain biological constraints. This paper aims to add to the idea of the defensive function of music, by looking at the role of pitch matching in the longdistance deterrence of conspecifics between singing hominins. Since the production and recognition of musical pitch depend on many abilities, their evolution in the context of this possible defensive function is discussed. In particular, the emergence and role of culturally variable musical pitch elements as hallmarks of group identity are examined when considering selective pressures that occurred from increasing hominin social complexity. In contrast to current monofunctional explanations, this proposal highlights a possible reinforcement between other adaptive functions of musical pitch related to the hominin social niche, which ultimately created a synergistic loop and accelerated the evolution of musicality.
Keywords: biomusicology; defense signaling; intraspecific defense; long-distance calls; musicality; musical pitch